2003
DOI: 10.1038/sj.onc.1206867
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene rearranged by 2p21 aberrations in thyroid adenomas

Abstract: Thyroid adenomas belong to the cytogenetically best investigated human epithelial tumors. Cytogenetic studies of about 450 benign lesions allow one to distinguish between different cytogenetic subgroups. Two chromosomal regions, that is, 19q13 and 2p21, are frequently rearranged in these tumors. Although 2p21 aberrations only account for about 10% of the benign thyroid tumors with clonal cytogenetic deviations, 2p21 rearrangements belong to the most common cytogenetic rearrangements in epithelial tumors due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 17 publications
0
70
0
1
Order By: Relevance
“…THADA is associated with epithelial thyroid adenomas (Rippe et al 2003); and genome wide association studies have implicated THADA alleles in type 2 diabetes (Zeggini et al 2008) and polycystic ovary syndrome (Chen et al 2011c). However, the biological significance of these associations is not known, and the linkage to Nm 32 modification remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…THADA is associated with epithelial thyroid adenomas (Rippe et al 2003); and genome wide association studies have implicated THADA alleles in type 2 diabetes (Zeggini et al 2008) and polycystic ovary syndrome (Chen et al 2011c). However, the biological significance of these associations is not known, and the linkage to Nm 32 modification remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the non-diabetogenic alleles or genotypes for the polymorphisms within KCNQ1, CDKN2A-2B, MADD, KCNJ11, THADA and FTO genes with the risk of MM suggests that these genes, rather than acting through an insulin-dependent mechanism, may modulate the risk of MM by acting as tumour suppressor genes (Duro et al 1995) or through mechanisms promoting cancer cell apoptosis (Rippe et al 2003, Turner et al 2013. In support of this idea, it has been recently reported that most of these genes are highly expressed in tumours and that genetic polymorphisms in these loci are also associated with cancer development (Sauroja et al 2000, Cander et al 2014) and tumour progression (Chen et al 2009).…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t another study, the Thada gene, a putative death receptor-interacting protein, was identified with the same approach on chromosome 2p21 of a thyroid adenoma cell line (Rippe, et al 2003). After reduction of data complexity, results are correlated with pathomorphology, molecular biological status such as B-raf mutation status or Ret expression status.…”
Section: New Candidate Genes In Thyroid Cancer Derived From Chromosommentioning
confidence: 99%